WAYS TO INCREASE THE ATTRACTIVENESS OF THE INVESTMENT ENVIRONMENT - Olimbekov Odilbek Saidmurod ugli (European Science Publishing, 2025)
The dynamics of key indicators determining the efficiency of investment funds have been analyzed. Issues of ensuring a favorable investment environment in our country and further increasing the influx of foreign capital have been discussed. Additionally, factors influencing the attraction of foreign investments and the global experience in addressing them have been studied.
Keywords: Investment, investor, foreign investment, foreign experience, Gross Domestic Product, direct foreign investment, ICOR indicator, attractiveness.